Less is more, greener microbial synthesis of silver nanoparticles - Liu, Lihong; Liu, T.; Tade, Moses; Wang, Shaobin; Li, X.; Liu, Shaomin (2014)
Microbial nano-synthesis has been well established as a green method for the sustainable development of nanotechnology. However, the mechanism of this biotechnology has to be reconsidered with the increasing realization that microorganism culture broth plays a vital role during the synthesis, which may obviate the dependence on microbes. Here, we demonstrate that silver nanoparticles (AgNPs) could be synthesized in several types of microorganism culture broth (an aqueous solution abundant in peptone, yeast extract from Saccharomyces cerevisiae, dextrose and other reducing and stabilizing agents) without any specific living microbe involvement. Light and high pH values of broth were identified as two critical factors in ensuring pure AgNPs formation. In broths containing NaCl at high concentration (0.5 wt%), silver chloride was identified as the major intermediate and could be converted to AgNPs via one-pot photoreduction. Our broth alone strategy dramatically simplifies the conventional microbial nano-synthesis process by cutting the use of microorganisms and thus provides a more eco-friendly way for nano-Ag preparation. The fundamental understanding of the microbial synthesis mechanisms and implementing of complete green methods to fabricate technologically important nanomaterials will be further promoted by this study.